Facile synthesis of anisotropic urchin-like Ni decorated reduced graphene oxide with enhanced impedance matching for effective electromagnetic wave absorption. (March 2022) - Wang, Yanping; Hao, Gazi; Hui, Zhenzhen; Zhang, Shaoqing; Ke, Xiang; Yan, Haoran
Abstract: To obtain the high-efficiency electromagnetic (EM) wave absorber, we synthesized a series of urchin-like Ni decorated reduced graphene oxide (urchin-like Ni/RGO) composites by a one-step method. The morphology and structure characterization results reveal that plenty of urchin-like Ni particles attached on the surface of RGO and their spiny protrusion are more pronounced than the pure urchin-like Ni. The EM wave absorption results indicate that the content of RGO directly affects their EM wave absorption performance. The effective absorption bandwidths of Ni/RGO-30 are 2.0 GHz and 2.3 GHz when the matching thicknesses are 2.0 mm and 2.5 mm, respectively. The optimal RL value of Ni/RGO-50 is − 34.8 dB with a matching thickness of 2.5 mm and the minimum RL values are all less than − 20.0 dB with the matching thicknesses of 2.0–5.5 mm. For Ni/RGO-70, the optimal RL value is −39.8 dB and the absorption bandwidth (RL ＜ −10 dB) is 2.7 GHz with 2.0 mm matching thickness. Such excellent EM wave absorption performance primarily comes from their strong dielectric loss capacity. Based on the EM wave absorption performance and mechanism analysis, it is believed that as-synthesized urchin-like Ni/RGO can be used as a promising EM wave absorber.